Pengembangan Integrasi Sapi-Kelapa Sawit Untuk Meningkatkan Taraf Hidup Petani Kecil Di Riau, Indonesia - I Gusti Ayu Putu Mahendri; Dwi Sisriyenni (Jurnal Riset Agribisnis dan Peternakan, 2020)
Cattle population in Indonesia has risen slowly during 2005-2019, while there is a significant increase in total beef consumption. To boost cattle population, the Government of Indonesia has encouraged the development of cattle integrated with palm-oil plantation through distributing cattle (mainly Brahman crosses imported from Australia) to farmers’ groups in some areas including Riau Province. However, this program has not significantly increased the cattle population or the numbers of farmers and companies participating in integrated cattle-palm oil production. This paper identifies the constraints and opportunities of cattle development in palm-oil areas in Indonesia particularly in Riau Province. Two farmers’ groups in Tapung District, Riau Province were interviewed using a semi-structured questionnaire to gain information related to their production, obstacles and the support they need to improve their cattle production. The main finding of the study is that farmers have received some benefits in addition to palm-oil production, in particular income from selling cattle to meet their secondary needs (school fees, wedding or land improvement), and manure on their plantation where cattle are grazed has reduced weeding cost. However, cattle management in palm-oil plantation could be improved, for instance by optimizing feed resources through improving access to palm-oil by-products; improve cattle feeding management through rotation strategies; and address reproduction issues through training to enhance farmers’ capability. Moreover, developing partnership with large producers and forming groups are possible ways to deal with issues in marketing such as difficulties in securing feeder and breeding cattle supply and low cattle price received by farmers.